2014
DOI: 10.5370/jeet.2014.9.3.978
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Dielectric and Thermal Characteristics of Nanosized Alumina Filler Added Polyimide Enamel

Abstract: -The polymer nano composite possess good priority recently for engineering applications.Especially the electrical insulating materials attract the high performance of nano composites. In this work the ballmill synthesiation process of nano sized Alumina (Al 2 O 3 ), the preparation of new nano composite material with an content of enamel and synthesized Alumina as 1wt%, 3wt% and 5wt%. Experimental investigation has been carried out for the prepared nano composites materials with respect to dielectric parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…It is reported that microfiller contents from 30 to 65% by weight are necessary to achieve the required electrical properties for outdoor insulation applications. Nanotechnology has introduced the applications of nano fillers to enhance the electrical and mechanical properties of the insulating materials [4][5]. One of the advantages of nano sized fillers is their large specific surface area when compared with micro fillers.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that microfiller contents from 30 to 65% by weight are necessary to achieve the required electrical properties for outdoor insulation applications. Nanotechnology has introduced the applications of nano fillers to enhance the electrical and mechanical properties of the insulating materials [4][5]. One of the advantages of nano sized fillers is their large specific surface area when compared with micro fillers.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the characteristic peak of the amide group (CONH) near 1660cm -1 is significantly weakened with the increasing of temperature, and it is faintly visible in the curve of 180°C, it is almost invisible in the curve of 240°C, and it is not seen in the spectrum curve of 300°C. These results indicate that the expected TPI polymer can be obtained by in-situ polymerization and thermal imidization [5,7] .…”
Section: Thermogravimetric Analysis(tga)mentioning
confidence: 58%
“…It indicates that the imidization degree of the sample increases with the temperature increasing, and the four distinct characteristic peaks of aromatic PI can be seen at 1721cm -1 , 1778cm -1 , 725cm -1 and 1373cm -1 . The strong absorption peaks around 1721cm -1 and 1778cm -1 are attributed to the symmetry and asymmetric stretching vibration of the imide group C=O in the TPI molecule, the peak at 725cm -1 may th be duo to the out-of-plane bending vibration of the imide group C=O, and the peak near the 1373cm -1 was caused by the stretching vibration absorption of the C-N-C in the imide bond [3][4][5][6][7] . At the same time, the characteristic peak of the amide group (CONH) near 1660cm -1 is significantly weakened with the increasing of temperature, and it is faintly visible in the curve of 180°C, it is almost invisible in the curve of 240°C, and it is not seen in the spectrum curve of 300°C.…”
Section: Thermogravimetric Analysis(tga)mentioning
confidence: 99%
“…There is likely to be strong bonding between the homogeneously dispersed alumina nanoparticles and the HDPE polymer which offers higher resistance to the stress on applying electric field, as a result the PD resistance of the composite increases. It has been noticed that for higher wt.% of nanoalumina added samples, the space in the interfacial zone increases thus reducing the PD resistance of the samples [3,[8][9][10]. The maximum inception and extinction voltages observed for 5 wt.% samples with a rise of 18.46% and 35.79%, respectively, in comparison with pure HDPE samples.…”
Section: Sample Preparationmentioning
confidence: 99%